Green energy generation from industrial wood waste: Pellet production from carbonised Eucalyptus saligna sawdust - Gemechu Y. Shage*, Dagnachew G. Demissu, Fikremariam H. Desalegn, Tegene T. Geta, Tatek D. Bekele, Mahelete T. Ayele, Tewabech A. Yetna, Abraham D. Gashaw, Tarekegn G. Admasu, Gemechu J. Morkato (Vietnam Journal of Science, Technology and Engineering, 2026)
This study investigated the potential of pellet production from carbonised E. saligna sawdust, processed at varying particle sizes (0.6 mm, 1.18 mm, and 2.36 mm) and utilising different organic binders. Proximate and ultimate analyses of charcoal pellets were investigated using standard test methods. E. saligna sawdust was carbonised using a cylindrical barrel metal kiln, and pelletised with a manual press machine using molasses, cow dung, and fruit waste as binding agents. The proximate and ultimate analyses of charcoal pellets were determined using American Society for Testing and Materials (ASTM). Binding agents significantly influenced moisture content, volatile matter, fixed carbon, ash content, calorific value, and sulphur content (p<0.001), while particle size had a moderate effect on select parameters, particularly fixed carbon and ash content. The highest fixed carbon (44.02%) and calorific value (4980 cal/g) were observed in cow dung-bound pellets, while fruit waste-bound pellets exhibited the lowest ash (3.82%) and sulphur content (0.12%), highlighting their environmental advantages. The interaction between binding agents and particle size was significant for moisture content and volatile matter but not for fixed carbon or calorific value. This research demonstrates an innovative approach to valorise plant waste materials and underscores the potential of local biomass for sustainable energy solutions.